Dural architecture of cavernous sinus. Structural Solid Marrow of the Sellyar Region - R. N. Lyunkova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Surgery of the base of the skull requires knowledge of the topography of the internal carotid artery, cavernous sinus, cranial nerves of the sellyar and paraclinoid regions. Equally important is knowledge of the topography and structure of the dura mater (CSF) at the base of the skull, CSF duplicates, cerebellar ligaments, meningeal membranes (tank membranes of the brain base, carotid oculomotor membrane of the proximal carotid ring) and carotid rings in neurooncology and vascular neurosurgery. The article presents the results of the study of the structure of TMO in the selvary and paraselar regions.